SOLVABILITAS PERUSAHAAN PERTAMBANGAN DITENTUKAN OLEH FIRM SIZE, SALES GROWTH DAN STRUKTUR AKTIVA - Edwin Agus Buniarto (STKIP PGRI Jombang, 2022)
The purpose of this study was to determine the effect of firm size, sales growth and asset structure on the solvency of mining companies listed on the Indonesian capital market. firm size, solvency is seen from the total assets of the company. Sales growth is measured using annual sales growth, and asset structure is measured using a comparison between fixed assets and total assets.The analysis of this study used multiple linear regression. The sampling technique used was random sampling method. By analyzing a sample of 36 samples obtained from 12 mining companies over the last 3 years, the results of the analysis are as follows:Firm size has a significant effect on the solvency of the company, with a regression coefficient of 0.2861. Sales growth has a significant effect on solvency with a regression coefficient of 0.4535. Asset structure has a significant effect on solvency with a regression coefficient of 0.0608. Simultaneously firm size, sales growth and asset structure have a significant effect on solvency with a coefficient of determination of 0.5678.